Como eventos paleoambientais e ecológicos moldaram a diversidade de lagartos neotropicais (Iguania: Leiosauridae) - Monjardim, Marina (2021)
The Neotropical Region is one of the most biodiverse regions on Earth and for reptiles is where the largest number of species and families occur. Several events shaped the biodiversity of this region throughout its evolutionary history, for instance, the formation of the Panama Isthmus, the Andes uplift, climate changes during the Plio-Pleistocene period. Moreover, several hypotheses were proposed to explain such diversity. Leiosauridae is a family of lizards (Squamata: Iguania) exclusively distributed in the Chilean and Brazilian subregions in the Neotropical region, and is closely related to Opluridae, distributed in Madagascar. To bring a greater understanding of the biodiversity in Neotropics and improve the understanding of the evolutionary history of Leiosauridae, we test hypotheses related to taxonomy, biogeography, and diversification rates and time, using a robust data from ultra-conserved elements (UCEs). We estimate the most complete phylogeny for Leiosauridae. With a dated species tree, we discuss about the taxonomy of this family, and the taxonomic status of its subfamilies, genera and species, and the relationship among them. Although a greater diversity is expected in tropical regions, we did not find differences between diversification rates among Chilean and Brazilian subregion clades. We found that for the deeper clades (subfamilies, genera, clades A and B of Enyalius, E. leechii, and D. darwinii and other species of Diplolaemus) those events related to the Oligocene/Miocene periods and the Andes uplift had more influence, while for the crown (species) it was the events of Plio-Pleistocene climate changes. The events triggered possibly by the Andes uplift, also seems to have had an influence on the distribution of these groups. Regarding Leiosaurinae, for example, after its origin in the extreme south of Patagonia, it seems that they dispersed towards the north possibly due to environmental changes. Furthermore, such events also influenced the current distribution of the Enyaliinae, as they contributed to the formation of the dry Diagonal, as the separation of the Atlantic Forest in north and south during the Miocene, an event older than that proposed in the literature. These findings bring a new point of view to improve the understanding of the evolutionary history of this family and of the Neotropical biomes.